Dollars Dollars Everywhere, Nor Any Dime to Lend: Credit Limit Constraints on Financial Sector Absorptive Capacity - Khwaja, Asim Ijaz; Mian, Atif; Zia, Bilal (Review of Financial Studies, 2010)
We exploit an unexpected inflow of liquidity in an emerging market to study how capital is intermediated to firms. We find that backward-looking credit limit constraints imposed by banks make it difficult for firms to borrow, despite readily available bank liquidity, healthy aggregate demand, and a sharply falling cost of capital. The resulting aggregate failure to extend and retain capital in the economy suggests that agency costs that force banks to rely on sticky balance-sheet-based credit limits prevent emerging economies from effectively intermediating capital.